2021
DOI: 10.1016/j.isci.2021.103135
|View full text |Cite
|
Sign up to set email alerts
|

Discovering a qualitative transcriptional signature of homologous recombination defectiveness for prostate cancer

Abstract: Summary The discovery of homologous recombination deficiency (HRD) biomarkers in prostate cancer is important for patients who will benefit from poly ADP-ribose polymerase inhibitor (PARPi). Here, we developed a transcriptional homologous recombination defectiveness (HRDness) signature, comprising 16 gene pairs (16-GPS), for prostate cancer by a relative expression ordering (REO)-based discovery procedure. Subsequently, two newly subtypes classified by 16-GPS showed a higher significance level in va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…HRD score was also found to predict the immunogenicity of BRCA1/2 breast cancer in the study by Kraya et al (2019). Li et al (2021) found that prostate cancer patients with high HRD had higher immune infiltration and immune checkpoint gene expression, suggesting that prostate cancer patients with high HRD may respond to immune checkpoint inhibitors (ICIs). These studies further supported our results and demonstrated that ICIs may be a promising treatment modality for LGG patients with high HRD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HRD score was also found to predict the immunogenicity of BRCA1/2 breast cancer in the study by Kraya et al (2019). Li et al (2021) found that prostate cancer patients with high HRD had higher immune infiltration and immune checkpoint gene expression, suggesting that prostate cancer patients with high HRD may respond to immune checkpoint inhibitors (ICIs). These studies further supported our results and demonstrated that ICIs may be a promising treatment modality for LGG patients with high HRD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, poly ADP-ribose polymerase (PARP) inhibitors were approved for use by the Food and Drug Administration and recommended for the treatment of tumors with BRCA1/2 mutations, including pancreatic cancer and prostate cancer (Rescigno et al, 2018;Li et al, 2021;Zhuang et al, 2021). Tumors with BRCA1/2 mutations are often accompanied by homologous recombination deficiency (HRD), and cancer cells with HRD are more sensitive to PARP inhibitors (Rescigno et al, 2018;Chen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Initially, this approach was used to calculate the HRD score in ovarian and breast cancer samples. Later, it was also extended to the analysis of other tumors in which BRCA1 and BRCA2 alterations are involved, such as pancreatic and prostate cancer [ 155 ] ( Table 2 ).…”
Section: Homologous Recombination Deficiency: a New Bioinformatics Ch...mentioning
confidence: 99%
“…Androgen receptor (AR) signaling plays a central role in both primary PCa and CRPC, and thus is the major pathway for the development of targeted therapy 3 . Recent large‐scale omics studies have identified additional oncogenic drivers and subtypes of PCa and CRPC, including gene fusion between the TMPRSS2 and ETS family members, loss of tumor suppressors P53 and RB1, SPOP mutation, activation of the PI3K signaling, among others 4–6 . In addition, single‐cell sequencing of patient tissues of different stages has greatly advanced our understanding of the heterogeneity and reprogramming of the PCa microenvironment throughout disease progression, potentiating therapeutic opportunities from both the immune and non‐immune compartments of the tumor niche 7,8 …”
Section: Introductionmentioning
confidence: 99%
“…3 Recent large-scale omics studies have identified additional oncogenic drivers and subtypes of PCa and CRPC, including gene fusion between the TMPRSS2 and ETS family members, loss of tumor suppressors P53 and RB1, SPOP mutation, activation of the PI3K signaling, among others. [4][5][6] In addition, single-cell sequencing of patient tissues of different stages has greatly advanced our understanding of the heterogeneity and reprogramming of the PCa microenvironment throughout disease progression, potentiating therapeutic opportunities from both the immune and non-immune compartments of the tumor niche. 7,8 Stressors in the tumor microenvironment such as hypoxia, nutrient unavailability, accumulation of reactive oxygen species, and low pH, can drastically perturb the homeostasis of endoplasmic reticulum (ER), causing ER stress.…”
Section: Introductionmentioning
confidence: 99%